Imperial state governance as a factor of social dynamics - Kirvel, Cheslav S.; Kirvel, Olga Ch. (Journal of the Belarusian State University. Sociology, 2023)
The article disclose the essence of the imperial form of government, which can represent an alternative to unipolar globalisation in the process of the historical development of society. An empire is understood as a sovereign state-civilisation, united by language, culture, ideology, specific goal-setting, certain modernisation programmes that are put forward and implemented by the power of the empire-forming people. The empire is interpreted as a form of peoples coexistence and is presented as a stable form of statehood and progress driver. The civilisational role of empires is emphasised and in its modern version, according to the authors, new empires as regional centres of power can be a prototype of the state structure of a multipolar world. The concept of a unipolar world is rejected, which is based on a linear-progressive, stage-by-stage understanding of world history. The authors’ concept of a multipolar world is based on a civilisational approach. It is proved that the civilisational role of empires is unthinkable without a unifying imperial form of statehood, fundamental differences between Western colonial and traditional continental empires, in particular the Russian Empire, are considered. In the Western empires with their colonial possessions, there was not only single geographical, but, first of all, a single socio-historical space, united by common values and culture. A promising form of the political structure of a multipolar world can be traditional historical empires of a centralised type or regional new empires, held together by a single territory, having a common cultural and ideological matrix, as well as a supranational unity, retaining their constant properties and features along with the ability to modernise and renew. It is shown that partial globalisation based on regional new empires takes on a new meaning and significance, becomes the key to a deeper understanding of the current situation in the world. In the author’s concept of a multipolar world, the new empire, based on a civilisational approach, can become the most effective form of government in the emerging regional centres of power. The concept of regionalisation proposed by the authors seems to be a very promising and fruitful line of scientific investigations.